INCIDENCE OF EXPENSES IN ACCOUNTING. - Winakor, Arthur H. (The Accounting Review, 1934)
A survey of the progress of accounting as a science quickly discloses that advancement in the field has been largely dependent upon an adequate differentiation among assets, expenses, liabilities, income, receipts, expenditures and the like. A correct separation of expenditures into assets and expenses on the one hand and of receipts into liabilities and income on the other hand, makes possible the attainment of modern accountancy and financial statements. The early systems of bookkeeping made no adequate distinction between expenses and assets and income and receipts. These items are intimately related and to differentiate among them means the correct calculation of profits and losses and financial conditions. A correct statement of assets cannot be made without a correct computation of expenses. Likewise, an accurate measure of income is not attainable without an adequate separation of income from receipts. If any one of these four items is incorrect, then either one or both of the two major financial statements must likewise be fallacious. Second only in importance to the recognition of the distinction among these items, is the determination of the moment when expense was separated from the assets and when the income arose in the assets.